2021
DOI: 10.3390/cancers13051023
|View full text |Cite
|
Sign up to set email alerts
|

Current Trends and Characteristics of Hepatocellular Carcinoma in Patients with Autoimmune Liver Diseases

Abstract: Hepatocellular carcinoma (HCC), the commonest among liver cancers, is one of the leading causes of mortality among malignancies worldwide. Several reports demonstrate autoimmune liver diseases (AILDs), including autoimmune hepatitis (AIH), primary biliary cholangitis (PBC), and primary sclerosing cholangitis (PSC) to confer increased risk of hepatobiliary malignancies, albeit at lower frequencies compared to other liver diseases. Several parameters have been recognized as risk factors for HCC development in AI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 148 publications
(61 reference statements)
1
31
0
1
Order By: Relevance
“…Of note is that signs of portal hypertension can develop even before the establishment of cirrhosis, which is presinusoidal in nature [ 66 ]. The risk of hepatocellular carcinoma (HCC) in PBC patients also increased, especially in men or those who have already developed cirrhosis [ 67 69 ].…”
Section: Diagnosis Of Pbcmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note is that signs of portal hypertension can develop even before the establishment of cirrhosis, which is presinusoidal in nature [ 66 ]. The risk of hepatocellular carcinoma (HCC) in PBC patients also increased, especially in men or those who have already developed cirrhosis [ 67 69 ].…”
Section: Diagnosis Of Pbcmentioning
confidence: 99%
“…In addition, an international cohort study showed that biochemical non-response at one year of UDCA treatment (Paris-II not fulfilled) significantly increased the future risk of HCC [ 172 ]. Other risk factors associated with HCC in PBC including older age, any signs of portal hypertension, thrombocytopenia, past HBV infection, diabetes, obesity and alcohol consumption, as summurized by two recent reviews [ 67 , 69 ].…”
Section: Management Of Pbcmentioning
confidence: 99%
“…HCC arises almost exclusively in the setting of chronic liver inflammation and, unlike the elevated risk associated with chronic viral (HBV and HCV) infections, it has been reported that the tumor is less common in liver cirrhosis caused by autoimmune liver diseases[ 12 - 15 ]. However, it is known that, regardless of etiology, cirrhosis per se represents a precancerous condition leading to an increased risk of HCC[ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…While PBC and PSC primarily involve biliary inflammation, autoimmune manifestations of AIH involve inflammation of the hepatic epithelium, characterized by hypergammaglobulinemia, circulating autoantibodies such as anti-nuclear antibody (ANA), anti-smooth muscle antibody (SMA) and high IgG titers [4]. The etiology of these AILDs remains unknown, but evidence suggests an amalgamation of genetic susceptibility and environmental risks [5], culminating in a loss of immune tolerance leading to the destruction of hepatocytes, which often end up into malignant conditions such as hepatocellular carcinoma (HCC) [6][7][8][9]. Common treatment modalities against AILDs involve immunosuppressant corticosteroid therapies, either as monotherapy or as combination therapy when co-administered with azathioprine [10].…”
Section: Introductionmentioning
confidence: 99%
“…Although the defined mechanism is still unclear, accumulating evidences suggest the AILDs to be key factors participating in HCC development [6][7][8][9]. Briefly, end-stage AILDs often lead to HCC, most likely due to the prolonged, robust hepato-inflammation.…”
Section: Introductionmentioning
confidence: 99%